An economic optimization modeling for sustainable water resources in agriculture: case of Tadla and Souss-Massa - F. Elame; H. Lionboui (African and Mediterranean Agricultural Journal - Al Awamia, 2022)
As for many other countries of the world, climate change is impacting drastically the water resources in Morocco and the consequences will be severe in our country for years to come. This situation generally results in a significant reduction in agricultural production, particularly in non-irrigated areas. It also has impacts on the availability of surface and underground water. Indeed, surface water supply experience a very important variation depending on the rainfall conditions and the favorable regions of Morocco generally located in the North present a less pronounced variation than those located in semi-arid and arid areas. This work was carried out in two regions of Morocco namely, Souss-Massa and Tadla. A dynamic optimization model was developed based on mathematical programming. The advantage of this type of model is its ability to reflect the relationship and links between various components (hydrologic, economic and agronomic) and to simulate the impact of any variable related to climate change or economic consequences due to policy choices. The main results of this work show that: (i) Surface and groundwater availability is decreasing in the two basins; (ii)The water resource shadow price increased in the two sites over time by changing from normal climatic conditions to drought conditions; and (iii) the reduction of some irrigated lands in favor of others more efficient and more profitable crops. Accordingly, the management of water resources should be based on integrated approaches in order to take into account the entire water cycle as well as the different actors involved in the use of this resource. The use of integrated water management policies is more efficient and will ensure the sustainability of water resource use activities, in particular the agricultural sector.